An Optimization of Load Frequency Control Based on Hydraulic Power Plant Using Transfer Function Balanced PID Controller - Delfianti, Rezi; Priyadi, Ardyono; Abadi, Imam; Setia Budi, Avian Lukman; Mustaqim, Bima; Andika, Yudi; Soeprijanto, Adi (International Journal of Integrated Engineering, 2021)
Power generator often rely on the stability and efficiency. For both active power and reactive power stability, it is needed a device that could control the power. In active power control, the output frequency must be controlled. Load frequency control has become a common solution for frequency control in hydraulic power generating units. The design of the load frequency control is still far from good but has succeeded in controlling the frequency back to normal at each load source and input. In this study, the proposed model is to use a PID controller that has been set with the Transfer Function Balanced tuning method. From the source input simulation results, the proposed model could fix the overshoot frequency by 71.929%. and reached rise time by 4.426 s. From the load input simulation results, the proposed model could fix the undershoot frequency by 58.974%. and reached rise time by 1.076 s.